Human metabolism and kinetics of tri-(2-ethylhexyl) trimellitate (TEHTM) after oral administration - Höllerer, Christine; Becker, Gunther; Göen, Thomas; Eckert, Elisabeth (Archives of Toxicology, 2018)
Tri-(2-ethylhexyl) trimellitate (TEHTM) is a plasticizer for PVC material and is used for medical devices as an alternative to di-(2-ethylhexyl) phthalate. As plasticizers are known to migrate easily into contact liquids, exposure of patients to TEHTM is highly probable. In the present study, human metabolism pathways of TEHTM and its elimination kinetics were investigated. For that purpose, four healthy volunteers were orally exposed to a single dose of TEHTM. TEHTM and its postulated primary metabolites were investigated in blood samples (up to 48 h after exposure), and in urine samples (collected until 72 h after exposure) using liquid chromatography tandem mass spectrometry (LC-MS/MS). TEHTM was found to be regioselectively hydrolyzed to its diesters di-2-(ethylhexyl) trimellitates (1,2-DEHTM, 2,4-DEHTM) with maximum blood concentrations at 3-h post-exposure, and to its monoester isomers mono-2-(ethylhexyl) trimellitates (1-MEHTM, 2-MEHTM) with peak blood concentrations 5-h post-exposure. For the elimination of investigated urinary metabolites, biphasic elimination kinetics was observed. The most dominant urinary biomarker was found to be 2-MEHTM (2-mono-(2-ethylhexyl) trimellitate), followed by several specific secondary metabolites. All in all, approximately 5.8% of the orally administered dose was recovered in urine over a period of 72 h, indicating a comparatively low resorption rate of TEHTM in humans in combination with an apparently rather slow metabolism and excretion rate. In fact, TEHTM and selected metabolites were still detectable in blood and urine 48-h and 72-h post-exposure, respectively. This study is the first to elucidate TEHTM metabolism pathways in humans and to identify metabolites of TEHTM in blood and urine by usage of especially designed human biomonitoring methods. Powerful tools for exposure monitoring and risk assessment of TEHTM are therewith available for future research.
EVALuna2:34676